Analisis Pengalaman Pengguna Pada Aplikasi Dompet Digital X Menggunakan User Experience Questionnaire - Hermawan, Yanto; Pratama, Pebi Paisal (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Digital wallet is an application that resides on a smartphone that can be used for transactions without using money cash. Referring to a survey conducted by Global Consumer insight (PwC, 2019), “Along with the growing number of active mobile internet users in Indonesia, the number of mobile payment users has also experienced growth.” One of the factors that influence user interest in continuing to use an application is the user's perception or experience. The purpose of this research is to determine the level of user experience aspects in the current X digital wallet, as well as determine aspects of the user experience that need to be improved using the User Experience Questionnaire (UEQ). “The population of this research is X digital wallet users using simple random sampling technique. Data analysis was performed using the UEQ Data Analysis Tool. The results of this study were found that the perspicuity aspect got a value of 1.25 or above average. The attractiveness, efficiency, dependability, and stimulation and novelty aspects respectively scored 0.90, 1.01 and 0.80, 0.89 and 0.52 or below average.” The recommendations in this study are expected to become one of the considerations for X digital wallet stakeholders to improve the X user experience. Keywords : Digital Wallet, User Experience, UEQ, UEQ Data Analysis Tool